KAZAKHSTAN, C.F.S. PROBLEMS OF AUTHENTICITY OF TEXTS OF NORMATIVE LEGAL ACTS IN THE KAZAKH AND RUSSIAN LANGUAGES (OF СIVIL CODE OF THE REPUBLIC OF KAZAKHSTAN AS AN EXAMPLE) - Akylbekova Гүлжан Кәрімқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
In article the problem questions arising at the translation of normative legal acts are considered.